Independent Community Building Model through Environmental-based Tourism Management in â€œMasdarlingâ€ Program - Yuli Gunawan; Bambang Eko; Reta Yudistyana; Dwi Thia Putri (Economics Development Analysis Journal, 2020)
Village tourism program is one of programs that can boost positive contributions to community development. This study aimed to design an independent community building model through environmental-based tourism management. Using primary and secondary data, the researchers used qualitative descriptive analysis to obtain a model of independent community building through environmental-based tourism management by forming a group named environmental awareness community group or Masdarling. In this way, regional potential can be used maximally, while masdarling tourism development was done using Community Based Tourism (CBT). A participative community empowerment became the main instrument to increase environmental living standard and preservation. Based on the mapping of problem patterns, the crucial programs to develop covered tourism awareness community, joint business group and integrated waste management efforts. It was expected that the development of tourism village through several kinds of village groups could explore various and sustainable tourism concepts. As a result, this development could fulfill the criteria of access, attraction, amenities. Upon this achievement, new tourism spots in Bontang City and the increase in community income can be obtained. Also, village economy and environment quality were resulted through the indirect effects of this development.